On Being a Marxist Muslim: Reading Hasan Raid's Autobiography - Ali-Fauzi, Ihsan (Studia Islamika, 2002)
In his recently published book, Clive Christie argues that Socialism, Marxism and Communism played a crucial role as weapons for Southeast Asian leaders in their fight against colonialism and as frameworks for them to run the newly independent nations. He also realizes that other ideologies such as those based on religion, which were older in terms of their coming into the region than the above-mentioned Western-originated ideologies, especially Islam in the Malay world and Confucianism and Buddhism in the Indo-China and Burma, also played a similarly important role. However, he provides only a dim analysis of the extremely intricate relationship between these types of ideology, especially between Marxism and Islam in the thought of leaders of movements such as the Islamic Union (Sarekat Islam or SI) in the then Dutch East Indies. Most probably for reasons of space, he makes only a slight, insignificant reference to SI.DOI: 10.15408/sdi.v9i1.675